SERVICE SYSTEMS WITH REPETITION OF APPLICATIONS WITH DETERMINED TIME OF STAY IN ORBIT - Коба, О. В. (Proceedings of National Aviation University (archive), 2021)
The research of modifications of queuing systems with repetition of applications after a determined time T is considered. Formulas of the basic indicators of efficiency of their functioning are received. The condition of ergodicity for the generalized system of L. Lakatosh GI/G/1 is derived.